The Shape and Presentation of the Catarrhine Talus: A Geometric Morphometric Analysis. Issue 6 (12th April 2013) - Turley, Kevin; Frost, Stephen R.
ABSTRACT The distal component of the talo‐crural joint, the talus, was compared, using geometric morphometrics, in 219 specimens from nine extant taxa to identify differences in shape and the factors influencing them. The specimens were laser scanned, digitally reconstructed, and landmarked. The whole talus, proximal and distal articular facet subgroups were analyzed using Generalized Procrustes analysis, linear regression, principal component analysis, analysis of percent variance, dot‐product vector analysis, and pair‐wise permutation tests to evaluate shape, and were visualized by TPS deformation of an exemplar surface. Significant percentages of shape variation among taxa were due to body mass, talar size, superfamily, and substrate preference. Shape and presentational morphology associated with these factors were documented, along with the similarities and differences among individual taxa. Nearly all taxa were significantly different in overall, proximal and distal shapes. The most important factors influencing whole talar shape were log centroid size and substrate preference. Substrate preference was also the most important factor defining proximal articular morphology and unrelated to other factor such as mass, while distal articular morphology was influenced by superfamily (head angle and shape). Results demonstrated that substrate preference and superfamily significantly influenced distal presentation, while substrate preference influenced proximal articular shape. Anat Rec, 296:877–890, 2013. © 2013 Wiley Periodicals, Inc.